The Relationship between Gastroduodenal Pathologies and Helicobacter pylori cagL (Cytotoxin-Associated Gene L) Polymorphism - Özbey, Doğukan; Demiryas, Süleyman; Akkuş, Seher; Kepil, Nuray; Dinç, Harika Öykü; Gareayaghi, Nesrin; Demirci, Mehmet; Kurt, Enes Ali; Uysal, Ömer; Sarıbaş, Suat; Tokman, Hrisi Bahar; Kocazeybek, Bekir (Turkish Journal of Gastroenterology, 2023)
Background: The polymorphisms in the region between 58 and 62 amino acids of the 194-amino acid CagL protein (CagL hypervariable motif) affect the binding affinity of CagL to integrin α5β1 (ITGA5B1) receptor in host epithelial cells and have an effect on the development of various gastrointestinal diseases. We aimed to evaluate the associations of gastroduodenal pathologies, with the polymorphisms of cagL gene of Helicobacter pylori (H. pylori) and also associations between vacA genotypes and cagL polymorphisms.Methods: A total of 19 gastric cancer, 16 duodenal ulcer, and 26 non-ulcer dyspepsia patients were included in this case-control study. All cases had H. pylori. A fragment of 651 bp from gene cagL (hp0539) and cagA, vacA genes was amplified by polymerase chain reaction. Purified polymerase chain reaction products were sequenced by Sanger sequencing, and nucleotide sequences were translated into amino acid sequences.Results: All of the H. pylori strains had cagL and cagA genes. In the 16 (84%) gastric cancer cases, the D58 amino acid polymorphism was significant than the 4 (15.4%) duodenal ulcer cases (P = .029), and the D58/K59 amino acid polymorphism was significant in 12 (63.1%) of the gastric cancer cases than 1 (3.85%) duodenal ulcer case (P = .008). D58/K59 and DKIGQ (n = 10; 52.63%) were the most common polymorphisms in the gastric cancer and were associated with the vacA genotype s1/m2, respectively (P = .022 and P = .008). The D58/K59 amino acid polymorphism was found to have a significant Odds Ratio (OR) value of 8.9 (P = .0017) in multivariate logistic regression analysis.Conclusions: The risk of gastric cancer development is 8.9 times higher with D58/K59 polymorphismCite this article as: Özbey D, Demiryas S, Akkuş S, et al. The relationship between gastroduodenal pathologies and Helicobacter pylori cagL (cytotoxin-associated gene L) polymorphism. Turk J Gastroenterol. 2023;34(4):346-355.